Indications of musical knowledge in the preliminary stylistic conceptions of graduate pianists: a quasi-experimental study (Orfeu, 2021)
This article aims to map indications of musical knowledge in the musical conceptions of style demonstrated in the speeches of young pianists at the graduate level in the preparation of three imposed works from different historical periods. A quasi-experiment was carried out with three piano students at Master and PhD degrees in Music, in which the participants learned musical works from different periods (18th, 19th and 20th centuries) and composers (Haydn, Chopin and Bartók) in three practice sessions. Interviews and records of works by participants allowed collecting conceptions for performances. The results showed consensus in conceptions of composers and styles on what the participants had already previous experience of practice of the repertoire (Haydn, Chopin), but in Bartók consensus was few. Thus, the present investigation brought evidences that the relational references of previous modes of musical expression, explicit organization of understanding (pre-conceived), as well as reception/perception as an interpreter-listener seem to be consistent indications of interconnecting stylistic knowledge and advancing perspectives of musical knowledge of instrumentalists in training.